Genetic markers of the risk of coronary heart disease and coronary artery thrombosis developing in the Kazakh population - Dana Taizhanova; Aliya Toleuova; Dmitry Babenko; Anar Turmuhambetova; Roza Bodaubay; Olga Visternichan; Akerke Kalimbetova; Ludmila Ahmaltdinova; Aigul Kurmanova (Babol University of Medical Sciences, 2023)
Background: Surgical methods such as coronary artery bypass grafting and percutaneous coronary interventions (PCI) are widely used along with traditional conservative therapy in the treatment of coronary artery disease. The disease outcome directly depends on timely diagnosis and treatment. A significant role in predicting the effectiveness of treatment is given to personification of treatment and management of the patient. In this case, the determining component is its individual genetic status. Methods: The study groups included persons of Kazakh nationality which identify themselves, their biological parents, and biological grandparents on the maternal and paternal side as Kazakh. Research groups included 108 people at the age from 45 to 65 years of both sexes. Blood samples genotyping was carried out by PCR using highly specific TaqMan samples. Thermo Fisher cloud application was used for genotypes determining on the base of an automatic algorithm. Results: The article presents the results of the evaluation of gene polymorphisms associated with coronary artery restenosis in a population of Kazakh nationality. 3 SNPs were determined when searching for an association with stenting due to coronary artery thrombosis: rs7543130 (p=0.009324), rs6785930 (p=0.016858), rs7819412 (p=0.061325). Conclusion: Four polymorphisms associated with the risk of developing coronary heart                        disease were revealed during the study of polymorphisms among the people of the Kazakh population. Three SNPs were determined when searching for an association with stenting due to coronary artery thrombosis. It should be noted that the Bonferonni correction for multiple comparisons did not reveal significant polymorphisms associated with coronary artery disease, which requires further research with more quantity of samples.